2022
DOI: 10.1136/bmjopen-2022-061599
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment and comparative analysis on the recommendations of current guidelines on screening and diagnosis of peripheral arterial disease: a systematic review

Abstract: ObjectivesThere are several clinical practice guidelines available for peripheral artery disease (PAD). The paucity of strong evidence is known to give room for variations in recommendations across guidelines, with attendant confusion among clinicians in clinical practice. This study aims to conduct a quality assessment and comparative analysis on PAD screening and diagnostic recommendations in PAD management.SelectionClinical practice guidelines written after 2010 and on or before 2020 were targeted. An exhau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…The AGREE II tool has previously been used to assess guidelines for pharmacological management and screening and diagnosis of PAD. 17 45 but in agreement with our results, found them to score higher in two of the three relevant domains than the NICE guidelines, 26 the American Heart Association/American College of Cardiology (AHA/ACC) guidelines 28 and the ESC guidelines. 18 The only domain where our results did not agree was applicability, where the AHA/ACC guidelines scored higher than the Global Vascular Guidelines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The AGREE II tool has previously been used to assess guidelines for pharmacological management and screening and diagnosis of PAD. 17 45 but in agreement with our results, found them to score higher in two of the three relevant domains than the NICE guidelines, 26 the American Heart Association/American College of Cardiology (AHA/ACC) guidelines 28 and the ESC guidelines. 18 The only domain where our results did not agree was applicability, where the AHA/ACC guidelines scored higher than the Global Vascular Guidelines.…”
Section: Discussionsupporting
confidence: 91%
“… 17 45 46 Uyagu et al , Chen et al and Barriocanal et al similarly found guidelines to score poorly in stakeholder involvement and applicability domains compared with clarity of presentation. The Global Vascular Guidelines 29 were only included in Uyagu et al ’s review of screening and diagnosis of PAD, 45 but in agreement with our results, found them to score higher in two of the three relevant domains than the NICE guidelines, 26 the American Heart Association/American College of Cardiology (AHA/ACC) guidelines 28 and the ESC guidelines. 18 The only domain where our results did not agree was applicability, where the AHA/ACC guidelines scored higher than the Global Vascular Guidelines.…”
Section: Discussionsupporting
confidence: 90%